Performance and Durability of High-Volume Fly Ash Concrete Incorporating Bacillus safensis : A Comparative Study of Class C and Class F Fly Ash - Iqlima Nuril Amini; Dzikrie Fikriyan Syah; Davin H. Ekaputra Setiamarga; Makno Basoeki; Luki Danardi; Irwanda Laory; Martin Anda; Mahendra Andiek Maulana; Meity Wulandari; Januarti Jaya Ekaputri (JACEE (Journal of Advanced Civil and Environmental Engineering), 2025)
This study investigates the performance and durability of high-volume fly ash (HVFA) concrete enriched with Bacillus safensis, focusing on the comparative influence of Class C and Class F fly ash. Concrete mixtures were prepared with varying proportions of both fly ash types, with and without microbial addition, and tested for fresh and hardened properties including compressive strength, splitting tensile strength, porosity, and workability. Durability was further evaluated using the rapid chloride penetration test (RCPT) and accelerated corrosion test (ACT).Results showed that Class C fly ash, with its higher calcium content, produced a denser microstructure and improved early compressive strength. In contrast, Class F fly ash supported more favorable long-term microbial activity due to greater porosity and water availability. Incorporating Bacillus safensis enhanced compressive strength by up to 8% and significantly reduced chloride ion penetration, particularly in Class F fly ash concrete, through calcium carbonate precipitation within the pores. However, microbial addition was associated with reduced splitting tensile strength, likely due to differences in failure mechanisms. Long-term observations revealed strength gains of up to 13.3% after one year in microbial HVFA concrete.These findings demonstrate the synergistic contribution of Bacillus safensis and the effect of fly ash type to the improvement of sustainability and durability of HVFA concrete.